Residivis Kejahatan Penyalahgunaan Narkotika Perspektif Teori Kontrol Sosial - M. Zidan Ardana; Maya Shafira; Firganefi Firganefi; Gunawan Jatmiko; Damanhuri Warganegara (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
Narcotics abuse is a very dangerous thing, because in addition to having an impact on the user's personal self, he will become addicted and his life will depend on narcotic substances, which if not prevented (treated), the type of narcotics that will be used will become stronger. and the larger the dose. Recidivism is the behavior of a person who repeats criminal acts after being sentenced by a judge's decision which has permanent legal force because of criminal acts that have been committed previously. The problem approach used is an empirical juridical method supported by a normative juridical approach. The data collection technique is that primary data is obtained through interviews with research subjects and secondary data is collected by reviewing through literature studies such as statutory regulations, books or literature, and journals. Data analysis uses qualitative data analysis. The factors that cause recidivism in narcotics abuse crimes are internal factors and external factors. Internal factors consist of uncontrollable desires, behavior, diligent praise, easily frustrated, and the character itself. External factors that cause someone to repeat the crime of narcotics abuse include environmental and social factors, economics, information and communication technology, and family factors. Efforts to overcome the recidivism of narcotics abuse that can be carried out are pre-emptive efforts, preventive efforts and repressive efforts.